Assessment of effectiveness degrees of the factors affecting the yield of some chickpea (Cicer arietinum) genotypes by path analysis - BABAGIL, GÜLÇIN EMEL (The Indian Journal of Agricultural Sciences, 2026)
The objectives of this study were to define direct and indirect correlations between the factors and the yield of four chickpea (Cicer arietinum L.) genotypes and to assess their effectiveness proportions in the Acological conditions of Erzurum by path analysis. The experiment was conducted on arid lands of Erzurum and Aziziye-94, Iþik, Cagatay and Yasa genotypes were used in this two-year experiment. Path analysis indicated the highest direct and positive effect of pod number (1.095), first pod height (0.574), and 100- seed weight (0.254) on seed yield. On the other hand, it indicated the direct and negative effect of plant length (-0.341), branch number (-0.383), seed number/pod (-1.311) on seed yield.